Trends and Return Frequencies of Hot and Cold Extreme Events in Northern Vietnam from 1961–2018 - Duc Thanh, Ngo; Thi Khanh Hoa, Bui (VNU Journal of Science: Earth and Environmental Sciences, 2023)
This study used observed data of maximum daily temperature (Tx) and average daily temperature (T2m) from 48 meteorological stations to investigate hot (SU35, Tx≥35 ºC), severe hot (SU37, Tx≥37 ºC), cold (FD15, T2m≤15 ºC), and severe cold (FD13, T2m≤13 ºC) events in Northern Vietnam from 1961 to 2018. Trends and frequency characteristics of SU35, SU37, FD15, and FD13 were calculated and discussed. Results showed a significant increase in the number of hot and severe hot days, while there was a notable decrease in the number of cold and severe cold days in the northern region of Vietnam. The North Central region experienced the highest increase in the number of severe hot days, ranging from 2  to 5 days per decade. In contrast, the Northwest and Northeast regions had the highest decline in the number of cold days, with  a rate of 3.5 to 4.5 days per decade for cold and 1 to 3 days per decade for severe cold days. The return values of Tx for the SU35 and SU37 thresholds for 10-year and 50-year return periods exceeded 41 ºC in the Northern Delta and North Central regions, which was higher than other regions (37–40 ºC). Meanwhile, the return values of T2m for the FD15 and FD13 thresholds were the lowest in the Northeast, typically ranging from 3 to 7 ºC for a 50-year return period. These results highlight the necessity of planning adaptation measures to address changes  in hot and cold extreme events, particularly in the key industrial areas of Northern Vietnam , in the context of climate change.   Keywords: Climate change, extreme hot and cold events, generalized Pareto distribution, trend analysis.